2003
DOI: 10.1385/bter:94:3:225
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Zinc and Vitamin A Can Alleviate Negative Effects of Heat Stress in Broiler Chickens

Abstract: This experiment was conducted to evaluate the effects of zinc (ZnSO4.H2O) and vitamin A (retinol) supplementation on performance, carcass characteristics, and serum concentrations of glucose, cholesterol, total protein, and malondialdehyde (MDA) as an indicator of lipid peroxidation in broiler chickens (Ross) reared at a high temperature (34 degrees C). One hundred twenty 10-d-old male broilers were randomly assigned to 4 treatment groups, 3 replicates of 10 birds each. The birds were fed either a basal diet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
56
5
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 35 publications
9
56
5
2
Order By: Relevance
“…Dietary amount and source of Zn in ducks diets increase in abdominal fat in other studies (Kucuk et al, 2003) could be the result of differences in species and dietary Zn content. In accordance with the findings in the present study, Sahin et al (2009) found that dietary Zn levels from 57 to 157 ppm fed to broilers from weeks 1 to 6 of age did not affect the percentage of dressed carcass or organ weights.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Dietary amount and source of Zn in ducks diets increase in abdominal fat in other studies (Kucuk et al, 2003) could be the result of differences in species and dietary Zn content. In accordance with the findings in the present study, Sahin et al (2009) found that dietary Zn levels from 57 to 157 ppm fed to broilers from weeks 1 to 6 of age did not affect the percentage of dressed carcass or organ weights.…”
Section: Discussionmentioning
confidence: 85%
“…In accordance with the findings in the present study, Sahin et al (2009) found that dietary Zn levels from 57 to 157 ppm fed to broilers from weeks 1 to 6 of age did not affect the percentage of dressed carcass or organ weights. However, Kucuk et al (2003) reported that 30 ppm dietary Zn significantly increased hot and chilled carcass weight, carcass yield and organ weights, compared with control groups.…”
Section: Discussionmentioning
confidence: 92%
“…Sahin et al (2002b) reported that dietary supplementation of chromium, improved feed intake, weight gain and feed efficiency of broilers exposed to high environmental temperatures. Zinc fortification was also shown to be beneficial in enhancing growth performance and carcase traits in heat-stressed broilers (Kucuk et al 2003). Thus, there is a possibility that broilers under hot environmental conditions require further VIT and TRM fortification in their diet.…”
Section: Introductionmentioning
confidence: 99%
“…Niu, Wei, Liu, Qin, Min and Gao reports (Sklan et al, 1994;Lessard et al, 1997;Kucuk et al, 2003). The growth performance of 42-day-old broilers was significantly reduced when the birds were raised under HS conditions.…”
Section: Discussionmentioning
confidence: 99%